Ethical and methodological challenges involved in research on sexual violence in Nigeria (2008)
Research on sexual violence is fraught with ethical and methodological challenges due to its sensitive nature. This paper describes the ethical and methodological challenges encountered in planning and conducting two exploratory studies on sexual violence that included in-depth interviews of eight female adolescent rape survivors in Ibadan and four married women in Lagos Nigeria who were raped, forced to perform sexual acts and sexually deprived. The first challenge encountered was an Institutional Review Board (IRB) requirement to obtain parental permission from adolescents, when such a requirement may place the adolescent at risk if a parent was a perpetrator of sexual violence. Using arguments emphasizing the Council for International Organization for Medical Sciences guidelines helped convince the IRB to provide a waiver of parental consent. Second, the privacy required to conduct in-depth interviews for rape survivors was difficult to achieve because five of the rape survivors were apprentices who work in public settings that which are typically used to conduct business In the informal sector. To overcome this challenge, interviews were conducted in safe locations, investigator's offices and homes of survivors. The culture of silence associated with sexual violence posed a challenge because it encourages perpetration of violence with impunity causing rape survivors to suffer in silence. None of the affected adolescents had sought judicial redress for rape despite availability of stringent punishment for this behaviour. Referral information was provided on where survivors could seek care. Interviews with the women could not be recorded on audio-tapes because of concerns that their partners might identify their voices from the tapes and punish them for this. Although research on sexual violence poses ethical and methodological challenges, it is not only desirable but also feasible to conduct such research in ways that ensure safety of participants.